(untitled) (Euro-Atlantic Studies New Series, 2025)
Sustainable development is at the core of every major decision in international politics, as the direction of the international community has been set towards protecting and restoring the resources of the planet. Although the goals are the same, each country is at a different level of achievement regarding the agreed-upon objectives. This article focuses on the current point Romania is in, the progress which has been made, and the path that lies ahead, analysed from the perspective of correcting measures that could help set its course on the right trajectory. Special attention is paid to the role that public participation has in implementing European policies designed to help the block follow through with its goal at the national level, in Romania. Considering that the literature is limited in this sphere, this article aims to connect some of the principal sustainable development pillars, contributing to the creation of a more complex picture of the actual context in Romania and the different dimensions that factor in the implementation of new policies.